Analisis Tindak Tutur Ilokusi pada Tuturan Film Pendek Berjudul Lemantun Sutradara Wregas Bhanuteja - Iin Iduljanah; Nia Ramadhani; Fika Yuni Lestari; Arinas Sa’adah; Alifia Shifa Latif; Laela Nabila; Asep Purwo Yudi Utomo; Nina Queena Hadi Putri (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Language functions as a means of communication used by humans to convey goals, ideas, ideas, emotions, and feelings to others. This research aims to identify and describe the types of illocutionary speech acts contained in the short film “Lemantun”. This research is categorized as descriptive qualitative research. The data source for this research comes from all the speech acts contained in the short film “Lemantun”. The data analyzed includes pieces of speech allegedly containing illocutionary speech acts from the short film “Lemantun”. The data collection method used in this research is the technique of free listening and note taking. The data source utilized is the short film “Lemantun” by utilizing the analysis of speech act types according to Searle, which includes representative, directive, expressive, commissive, and declarative. This article can be useful for students because it provides knowledge about the types of illocutionary speech acts, so it is hoped that students can identify various types of illocutionary speech acts in daily activities.